STRUCTURAL MODEL IN ASSESSING INTERRELATIONSHIP BETWEEN INTERNAL AND EXTERNAL FACTOR TOWARD MATHEMATICS LEARNING ACHIEVEMENT OF THE TENTH YEAR STUDENTS OF PUBLIC SENIOR SECONDARY SCHOOL IN MAKASSAR CITY - Syukriani, Andi (Universitas Negeri Makassar, 2013)
The main problem to be considered in this research is how the inter-relationship between internal factors (self-concept of mathematics and interest in learning) and external factors (parent's parenting and learning facilities) on mathematics learning achievement of grade X SMA students in Makassar city. The population in this study are all students of class X SMA Negeri in Makassar city. Data were collected through 348 selected samples with stratified random sampling technique, using a scoring scale and a mathematics learning achievement test that was structured as a research instrument. Data analysis begins with validation and instrument reliability test through confirmatory factor analysis, followed by model verification to obtain final structural model of stage. Finally, intervening variable mediation analysis is performed on the final structural model. The result of the research gives an idea that the self concept of mathematics of class X students of SMA Negeri in Makassar is in the category whereas the interest of learning mathematics of X class student of SMA Negeri in Makassar is in high category. Then the democratic upbringing of students of class X State Senior High School in Makassar is in the good category while the learning facilities of students of class X State Senior High School in Makassar are in very complete category. The achievement of mathematics learning of grade X of SMA Negeri in Makassar is in the less category. The results of the study also provide support to the proposed applicative model which illustrates that the higher the integration of internal factors (especially the self-concept of mathematics and interest in learning mathematics) and external factors (especially the democratic parenting and learning facilities) will be higher the level of mathematics achievement of grade X Country in the city of Makassar